Frequency and Predictors of Sleep Disorders in Undergraduate Medical Students - Zainab, Saima; Soomro, Rafiq Ahmed; Khoso, Aneeta; Qazi, Nimra Aziz (Journal of Liaquat University of Medical & Health Sciences, 2020)
Objective: To assess frequency of sleep disorders among the medical students and to explore the association between different predictors and sleep disorders among the medical students. Methodology: This cross-sectional study was conducted from September 2016 to December 2017 at Liaquat National Medical College Karachi, Pakistan. The study used 31% as prevalence of poor quality of sleep among medical students in Pakistan as identified in a previous research and 95% confidence level. The largest sample size calculated was n= 329. To adjust for the 10% expected non-response from some students, the final sample size was increased to 360 medical students. Non-probability purposive sampling technique was employed to recruit medical students. Students having systemic diseases, clinically diagnosed psychiatric problems and addiction, or those who refused to be part of the research were excluded. Internationally validated questionnaires were used for data collection which included Insomnia Severity Index, Depression Anxiety Stress Scale, Berlin Questionnaire and Epworth Sleepiness Scale. Results: Mean age of students was 21.98 years. Majority of them were females. Over 50% of students used internet more than 4 hours daily. One-third 36.3% (131) medical students obtained higher than normal scores on stress scale and 46% (167) on anxiety scale. The frequencies of students on risk of sleep disorders were as; day-time sleepiness 34%, obstructive sleep apnea 20% and insomnia 17%. The predictors of sleep disorders were male gender, excessive internet use and anxiety. Conclusion: The considerable frequency of medical students is at risk of developing sleep disorders. The likelihood is more for male students and excess internet use.